Effectiveness of Zanthoxylum piperitum-derived essential oil as an alternative repellent under laboratory and field applications - Kamsuk K. (2014)
Recently, there were considerable efforts made to promote the use of environmentally friendly and biodegradable natural insecticides and repellents, particularly from botanical sources. In this study, Zanthoxylum piperitum-derived essential oil isolated by steam distillation was investigated and compared to the standard synthetic repellent, N,N-diethyl-3-methylbenzamide (DEET), for repellency against mosquitoes under laboratory and field conditions. The oil of Z. piperitum alone and also with 5% vanillin added repelled laboratory-reared female Aedes aegypti with the median protection times of 1.5 and 2.5 h, respectively. These repellency times were proven to be significantly lower than those of DEET-based products: 25% DEET and 25% DEET + 5% vanillin demonstrating 3.5 and 5.5 h, respectively. However, when applied under field conditions, Z. piperitum oil + 5% vanillin was found to provide better protection against a wide range of natural mosquito populations than 25% DEET + 5% vanillin. While the product of DEET was effective in reducing bites with 99.7% protection, the protective effect of Z. piperitum oil product appeared complete (100%). It had a protective effect against Aedes gardnerii, Anopheles barbirostris, Armigeres subalbatus, Culex tritaeniorhynchus, Culex gelidus, Culex vishnui group, and Mansonia uniformis. The better repellency against a wide range of field mosquitoes derived from Z. piperitum oil products suggested an advantage of efficacy by providing a broad spectrum of activity. Therefore, Z. piperitum could have potential for use in the development of combined repellents as a natural active ingredient, synergist, or additive to conventional synthetic chemicals, particularly in situations when DEET is ineffective and impractical. © 2006 Springer-Verlag.